Examining the Impact of the World Health Organization 2022 Guidelines on Evaluation of Biosimilars for Non-Local Comparators in Biosimilar Studies on Middle East and North Africa Member States - Michael W. Strand; Jonathan H. Watanabe (MDPI AG, 2024)
Global support and standardization of regulation for biosimilars approval owes much of its legacy to the World Health Organization (WHO), since the first guidance by the organization on the matter was released in 2009. Since then, and with over a decade of research, the 2022 revision provides opportunities for time and financial savings to pharmaceutical manufacturers aiming to prove similarity of a potential biosimilar product to some reference product, particularly by clarifying that the use of a non-local reference product as a comparator in certain studies is permissible. This declaration has important implications, particularly in the emerging biological markets of the Middle East and North Africa region, where WHO guidelines have been integral to the regulatory framework of over a dozen countries for more than a decade. This article aims to review the impact of this revision on these countries and relevant policies on non-local comparator usage. Since 2022, this revision has been adopted only in Egypt. Many North African countries are yet to adopt a first draft of the formalized guidance. This analysis revealed that, although many of these countries reference the WHO guidelines, hesitation remains in terms of sourcing comparator products outside the US or European countries. This likely translates to slow regional development and cooperation of functioning, sustainable biosimilars markets. Future studies will be necessary to evaluate the continued development of guidance within these countries and changes in comparator sourcing norms as more time is allowed for their policies to mature and adapt to new standards.